Design and Additive Manufacturing of a Biomimetic Customized Cranial Implant Based on Voronoi Diagram - Sharma, Neha; Ostas, Daniel; Rotar, Horatiu; Brantner, Philipp; Thieringer, Florian Markus (Frontiers in Physiology, 2021)
Reconstruction of cranial defects is an arduous task for craniomaxillofacial surgeons. Additive manufacturing (AM) or three-dimensional (3D) printing of titanium patient-specific implants (PSIs) made its way into cranioplasty, improving the clinical outcomes in complex surgical procedures. Besides, there has been a significant interest within the medical community in redesigning implants based on natural analogies. In this paper, we propose a workflow to create a biomimetic patient-specific cranial prosthesis with an interconnected strut macrostructure mimicking bone trabeculae. The method implements an interactive generative design approach based on the Voronoi diagram or tessellations. Furthermore, the quasi-self-supporting fabrication feasibility of the biomimetic, lightweight titanium cranial prosthesis design is assessed using Selective Laser Melting (SLM) technology.